The role of sickness in the evaluation of job search assistance and sanctions - Gerard J. Van den Berg; Barbara Hofmann; Arne Uhlendorff (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Unemployment insurance agencies may combat moral hazard by punishing refusals to apply to assigned vacancies. However, the possibility to report sick creates an additional moral hazard, since during sickness spells, minimum requirements on search behavior do not apply. This reduces the ex-ante threat of sanctions. We analyze the effects of vacancy referrals and sanctions on the unemployment duration and the quality of job matches, in conjunction with the possibility to report sick. We estimate multi-spell duration models with selection on unobserved characteristics. We find that a vacancy referral increases the transition rate into work and that such accepted jobs go along with lower wages. We also find a positive effect of a vacancy referral on the probability of reporting sick. This effect is smaller at high durations, which suggests that the relative attractiveness of vacancy referrals increases over the time spent in unemployment. Overall, around 9% of sickness absence during unemployment is induced by vacancy referrals.
Keywords: J64; J65; C41; C21; 330; unemployment; vacancy referrals; physician; wage; unemployment insurance; monitoring; moral hazard